KEKUATAN SAMBUNGAN TEGAK (BUTT JOINT) STRUKTUR BALOK LAMINASI (GLULAM BEAMS) DARI KAYU LOKAL - Ratna Widyawati (UNIVERSITAS LAMPUNG, 2010)
In a line with technology growth in wood working and manufacturing, the require of raw materialwoodhighly increase. That’s why the efforts for raising the efficient of wood as one ofconstruction materials is needed. One of the alternatives is using low quality wood of fast growingwood with laminating technology. This study purposed to find out the optimum strength of scarfjoint using resin Urea Formaldehyde and the influence of kemiri (Aleurites moluccana willd)glulam beam towards the strength. The specimen of glulam beam has size of 75 mm in width, 125mm in thickness, and 2500 mm in length, with two variation of butt joint placement. Threespeciments are used in each variation of butt joint placement. Slices of Kemiri wood are laminatedusing Urea Formaldehyde (UA-104) glue with the thickness of 40/MDGL. The test is carried outby giving lateral static load on the specimen gradually until the crack of the specimen. The testindicates that the variation of butt joint placement has no effect to its strength. The averagemaximum strength of glulam beam BLK 1 is 1570,24 kg; BLK 2 is 1498,78 kg; while for BLKS 3is 1332,21 kg. If compared to the strength of solid beams of Kemiri wood that is 1093,94 kg,glulam beam has more strength of 34,11 %. The crack of glulam beams in the tests is started onthe stress area. The crack is continued on the strain area and followed by the fracture in thebottom of the wood.